Survey of parasites on Puntius sealei (Genus Barbodes) at disturbed and undisturbed water sources in Kuching Division, Sarawak - Noradilla, Mahmod (Universiti Malaysia Sarawak (UNIMAS), 2017)
Parasites are the microscopic living organisms that require host for them to continue living. There is lack of research studies on parasites infestation on freshwater fish especially on Puntius sealei. Also, there is lack of comprehensive studies of the fish parasites in comparison to their environmental water conditions in Borneo. This study aimed to identify the abundance of parasites on Puntius sealei at disturbed and undisturbed water sources, to correlate the infestation of parasites on Puntius sealei with water quality and to identify the infestation of parasites with the body size of the fish. Parasites studies conducted on Puntius sealei in four sampling locations representing two different types of water sources (i. e. disturbed and undisturbed water sources) in Kuching division, Sarawak from November 2016 - January 2017. A total of 60 host fish of P. sealei were examined and water quality parameters were taken during the study period. A total of 33 (55%) fishes were observed to be infested by parasites. Out of 33 individuals of fish infested, only seven (21.2%) fishes infested with ectoparasites and 26 (78.8%) fishes infested with endoparasites. A total of 74 individuals of parasites were recovered from the infested hosts. Three different groups of parasites namely endoparasite Nematoda (unidentified), ectoparasite Digenea (Transversotrema sp. ) and endoparasite Acanthocephala (Pallisentis sp. and Acanthocephala a) were identified. Most of the parasites were collected from intestines and only one parasites collected at the skin (scales). From this study, there is no significant difference between water quality and parasites infestation. This study show that the larger the fish body size, the higher the parasitic infestation of Puntius sealei. This research can become a baseline study on parasitic infections of Puntius sealei which is known to be endemic species in Borneo.